The Effect Of Accounting System On The Effectiveness Of Internal Control At PERUMDA Air Minum Tirta Medal Sumedang - Epilia Yunita; Erpi Rahman; Maman Nurochman (LPPM Universitas Sebelas April, 2020)
The background of this study is that the researchers see that the internal control of fixed assets in PERUMDA Air Minum Tirta Medal Sumedang has not run optimally, this can be seen from various problems related to weak control over fixed assets. This study aims to examine and obtain evidence regarding the fixed asset accounting system that affects the effectiveness of fixed asset internal control. The method used in this study is a quantitative research method with a survey approach. This study uses primary data and secondary data sourced from PERUMDA Air Minum Tirta Medal Sumedang. The samples used were 20 samples. Determination of the sample using purposive sampling technique. The data collection technique was obtained from the results of interviews, questionnaires, observations, and library research. Furthermore, testing of validity, reliability, spearman rank correlation, coefficient of determination, and hypothesis testing were carried out. The results showed that the fixed asset accounting system had a significant effect on the effectiveness of fixed asset internal control. Respondents' assessment of the fixed asset accounting system and the effectiveness of internal control is in the very strong category. The relationship between the fixed asset accounting system and the effectiveness of internal control shows a strong correlation. Respondents' assessment of the fixed asset accounting system and the effectiveness of internal control is in the very strong category. This shows that the hypothesis proposed by the researcher is